A cost-effective technique for generating preservable biomass smoke extract and measuring its effect on cell receptor expression in human bronchial epithelial cells. Issue 1 (4th October 2018) - Rajendra, K C; Zosky, Graeme R; Shukla, Shakti D; O'Toole, Ronan F
Abstract: Nearly half of the world's population uses biomass fuel for the purposes of cooking and heating. Smoke derived from biomass increases the risk of the development of lung diseases, including pneumonia, chronic obstructive pulmonary disease, airway tract infections, and lung cancer. Despite the evidence linking biomass smoke exposure to pulmonary disease, only a small number of experimental studies have been conducted on the impact of biomass smoke on airway epithelial cells. This is in part due to the lack of a standard and easily accessible procedure for the preparation of biomass smoke. Here, we describe a cost-effective and reproducible method for the generation of different smoke extracts, in particular, cow dung smoke extract (CDSE) and wood smoke extract (WSE) for use in a range of biological applications. We examined the effect of the biomass smoke extracts on human bronchial epithelial cell expression of a known responder to cigarette smoke exposure (CSE), the platelet-activating factor receptor (PAFR). Similar to the treatment with CSE, we observed a dose-dependent increase in PAFR expression on human airway epithelial cells that were exposed to CDSE and WSE. This method provides biomass smoke in a re-usable form for cell and molecular bioscience studies on the pathogenesis of chronic lung disease.